Analysis of Village Infrastructure Development Planning Based on the conditions and potential of the area in Baumata Timur Village, Taebenu District, Kupang Regency in 2023 - Maria Goreti Susanti; Fransina W. Ballo; Olivia L.E Tomasowa (Universitas Dharmawangsa Medan, 2026)
Infrastructure development is a crucial aspect in efforts to improve the welfare of rural communities. Based on Law No. 6 of 2014 concerning Villages, villages have the authority to manage their own natural resources and potential to improve community welfare. However, rural infrastructure development still faces various challenges, including disparities between infrastructure sectors. This study aims to analyze village infrastructure development planning based on regional conditions and potential in East Baumata Village, and evaluate the effectiveness of Musrenbang in the planning process. This study uses a qualitative approach with a descriptive research type. The results show that the condition of infrastructure in East Baumata Village shows disparities between sectors. Road infrastructure is still not optimal with damaged, bumpy, and potholed conditions which are the main complaints of the community. In contrast, clean water and irrigation infrastructure are relatively adequate and managed through BUMDes. The village's potential lies in the agricultural sector (rice fields 40.5 ha/m2) and livestock, which are the main livelihoods of the community. Development planning has taken into account regional conditions and potential as reflected in the RPJMDes and RKPDes, but still faces budget constraints in its implementation. The implementation of the Musrenbang (Village Development Planning) has involved active community participation, but its effectiveness has not been optimal due to limited village fiscal capacity. Keywords: Village Infrastructure, Development Planning, Regional Potential, Effectiveness of MusrenbangDes